Antiplatelet therapy: new pharmacological agents and changing paradigms. (30th June 2013) - Capodanno, D.; Ferreiro, J. L.; Angiolillo, D. J.
Summary: Recurrent atherothrombotic events in patients with acute coronary syndromes (ACS) and/or those undergoing percutaneous coronary intervention (PCI) are essentially platelet‐driven processes, underscoring the need for effective pharmacological platelet inhibition. Dual antiplatelet therapy with aspirin and clopidogrel has been, for over a decade, the mainstay of antiplatelet management in ACS/PCI. However, atherothrombotic events continue to occur in a relevant proportion of subjects despite the benefit of this combination, which has led to the clinical development of newer and more potent antiplatelet drugs. Two of these, prasugrel and ticagrelor, have been recently approved for clinical use. The scope of this manuscript is to provide an up‐to‐date overview on new antiplatelet drugs in the setting of ACS and PCI, including the most recent advances on newly approved agents as well as on emerging compounds in clinical development.